Gender Advocacy in Lawrence’s Women in Love - Adhikari, Rajan (Haimaprabha, 2025)
This research work makes an attempt to explore how patriarchal ideology exploits the female characters in D.H. Lawrence’s Women in Love. It uses the perspective of Marxist Feminism which advocates for the end of economic exploitation of women. In Women in Love Ursula and Gudrun struggle to liberate themselves from the Capitalist patriarchal domination they suffer from at the hands of males in the contemporary British patriarchal society. This research stays significant within the context of scholarship in the sense that it attempts to impart a deep insight regarding how the effects of patriarchal ideology exploits the female characters and finally how they struggle to liberate themselves from patriarchal domination. Similarly, I have used D. H. Lawrence’s Women in Love as a primary text to show how Ursula and Gudrun struggle to liberate themselves from the male domination. Marxist Feminism focuses on the ways that women are oppressed through capitalist economic practices. According to this theory, women are exploited in the home and in the workplace because much of their labor is uncompensated.